PENGARUH PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PRODUK ES BATU PADA PT. AGRONESIA DIVISI INDUSTRI ES SARIPETOJO BANDUNG - Intan Kurniawan; I Ketut Martana (Universitas Bina Sarana Informatika, 2017)
every company will go through any means to increase sales by encouraging poensial consumer to speed up their purchasing decision. Puchase desicion is an act of potential consumer to decide to buy or not a product that is being offered. Ice Cube Industry Division in PT. Agronesia Saripetojo, Bandung branch has considered marketing communication factor that influence purchashing decision, one of them is personal selling activities. This research aimed to determine the effect of personal selling’s on ice cube purchasing desicion at PT Agronesia. The proposed hypothesis shows a significant personal selling impact on purchasing desicion’s. The research used survey method with sample of 70 people as respondent. The type of this research’s explanatory research, the data are compiled through the distribution of questioner using the likert scale. The data analisis method used is pearson colerations, simple and multiple linier regression using the SPSS 21 program. This research concluded that there is a significant impact of personal selling on perchasing decision. Key Word : Personal selling, Purchasing decision